2008
DOI: 10.1080/10810730802279571
|View full text |Cite
|
Sign up to set email alerts
|

News Coverage of Cancer in the United States: A National Sample of Newspapers, Television, and Magazines

Abstract: A content analysis of cancer news coverage in a sample of local and national newspapers, television, and magazines was conducted for the years 2002 and 2003. Analyses compared proportions of mentions of cancer sites with proportional contribution to cancer incidence and mortality based on available epidemiological estimates. Analyses also examined relative attention provided to prevention, detection, treatment, causes and outcomes of various cancers. Results indicated that coverage reflected incidence rates mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
111
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(139 citation statements)
references
References 36 publications
21
111
5
2
Order By: Relevance
“…The current study replicates and extends current work (e.g., Cohen et al, 2008;Slater et al, 2008) as well as links back to the original comprehensive content analyses by using a comparable content scheme. This approach may reveal trends that ultimately contribute to individual or societal illness representations (e.g., about cancer risk factors).…”
Section: Content Analyses Of Cancer News Coveragesupporting
confidence: 64%
See 1 more Smart Citation
“…The current study replicates and extends current work (e.g., Cohen et al, 2008;Slater et al, 2008) as well as links back to the original comprehensive content analyses by using a comparable content scheme. This approach may reveal trends that ultimately contribute to individual or societal illness representations (e.g., about cancer risk factors).…”
Section: Content Analyses Of Cancer News Coveragesupporting
confidence: 64%
“…This work generally has shown that cancer news coverage mirrors incidence rates rather than mortality rates; however, certain cancers (e.g., breast cancer) disproportionately are represented regardless of the comparison data (Cohen et al, 2008;Hoffman-Goetz & Friedman, 2005;Slater, Long, Bettinghaus, & Reineke, 2008).…”
mentioning
confidence: 99%
“…이 뉴스 미디어의 환경 감시 기능은 환경오염 (Ader, 1995), 범죄 (Sheley & Ashkins, 1981), 경제 (Ju, 2008;Soroka, 2006) 등 특정 이슈의 언론 보도라는 틀 속에서 연 구가 진행되었다. 예를 들어, 에더 (Ader, 1995) Freimuth et al, 1984;Greenberg, Freimuth, & Bratic, 1979;Hoffman-Goetz & Friedman, 2005;Jensen, Moriarty, Hurley, & Stryker, 2010;Slater, Long, Bettinghaus, & Reineke, 2008) (Ju, 2008;Soroka, 2006), 환경오염 (Ader, 1995), 범죄 Health and Social Behavior,41, …”
Section: 언론 환경 감시 기능의 적절성이라는 차원에서의 접근 은 뉴스미디어가 원래 사회에 잠재된 위험 요인들에 대한 unclassified
“…Possibly most importantly, Slater et al (ref. 25, p. 534) find "numerous disparities between cancer news coverage and the realities of the disease in the United States" (25).…”
Section: Patterns Of Scientific Information In Media Contentmentioning
confidence: 99%